Reconhecimento jurídico da união estável homoafetiva na perspectiva dos direitos fundamentais - Duarte, Renata Stauffer (2011)
Both society and the conception of the family have been transformed over the years, and this, before structured on patriarchy, became an attractive location for emotional fulfillment of its members. As a result of these developments, the prejudice toward homosexuality has gradually decreased, which nowadays result in unions between same-sex couples, who already presenting themselves publicly in social circles. In Brazil, the pinnacle of legal developments related to families came to fruition with the promulgation of the Constitution of 1988, which in its art. 226, declared the existence of a plurality of family entities, among them, the stable union between a man and woman. It was also the 1988 Federal Constitution that established in Brazil the democratic state, when the fundamental rights of human dignity, equality and freedom embody a new meaning and greater relevance. The Constitution, based on its normative aspect and supremacy, must be obeyed by everyone, including state agencies and its precepts shall be the basis for interpretation of other rules. However, despite the homo marriage being a reality in society, often, the Judiciary does not recognize it as a family, with a narrow construction of Art. 226 CF and taking as a principle constitutional outdated paradigms to discriminate homosexuals and their relationships, preventing the achievement of the objectives of the Federative Republic of Brazil of building a free society, with justice and solidarity. To correct this injustice, the art. 226 of the Constitution shall be applied in accordance with the principles mentioned above, construing the law in its integrity, which only turns to the past when directed by its contemporary focus. Therefore, this paper addresses the possibility of recognizing the union between persons of same sex as a familiar entity constitutionally protected, even if no explicit law specifying it as such, by applying the principles of human dignity, equality and freedom. The deductive method used as source and methodological basis of this study was to literature, drawing on the teaching of renowned authors on the subject.